Influence of overnight orthokeratology on tear film and meibomian glands in myopic children: a prospective study - Jing Ruan; Yu Zhang; Yueguo Chen (BMC Ophthalmology, 2023)
Abstract Background Orthokeratology lenses, which are worn overnight, are recommended for reducing myopia progression. They lie on the cornea and can influence the ocular surface by temporarily reshaping the corneal surface through a reverse geometry design. This study investigated the effect of overnight orthokeratology lenses on tear film stability and meibomian gland status in children aged 8–15 years. Methods This prospective, self-controlled study included 33 children with monocular myopia who were prescribed orthokeratology lenses for at least one year. The experimental group (ortho-k group) comprised 33 myopic eyes. The control group comprised the emmetropic eyes of the same participants. Tear film stability and meibomian gland status were measured using a Keratograph 5M (Oculus, Wetzlar, Germany). Paired t-tests and Wilcoxon signed-rank tests were used to compare the data between the two groups. Results At the one-year visit, the non-invasive first tear film break-up time (NIBUTf) values were 6.15 ± 2.56 s and 6.18 ± 2.61 s in the experimental and control groups, respectively. The lower tear meniscus height was 18.74 ± 0.05 μm and 18.65 ± 0.04 μm in these groups, respectively. No significant difference was observed in loss of meibomian glands or non-invasive average tear film break-up time between the experimental and control groups using Wilcoxon signed-rank tests. Conclusions The stability of the tear film and meibomian gland status were not significantly affected by wearing orthokeratology lenses overnight, indicating that continuous use of orthokeratology lenses for 12 months has a minimal effect on the ocular surface. This finding can help guide the clinical management of tear film quality with respect to the use of orthokeratology contact lenses.